2009
DOI: 10.1007/s12070-009-0038-0
|View full text |Cite
|
Sign up to set email alerts
|

Fourth branchial pouch sinus — an unusually late initial presentation

Abstract: Objective Here we present an unusual case of a male patient with 4th branchial pouch sinus with an initial presentation of pseudothyroiditis at an unusually late age of 20 years.Method Case report and a review of the world literature concerning 4th branchial pouch sinus is presented.Result The patient was diagnosed by radiology and endoscopy and treated surgically. Histopathology revealed chronic infl ammatory changes, which pointed towards recurrent sub clinical low-grade infl ammations over the years keeping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Fourth branchial anomalies typically manifest in the first decade of life and usually have a long history of recurrent neck lesions which are refractory to treatment [ 9 ]. Stadler et al reported a case of recurrent neck infections with long-term misdiagnosis for 24 years before the correct diagnosis of fourth branchial cleft anomaly was made [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fourth branchial anomalies typically manifest in the first decade of life and usually have a long history of recurrent neck lesions which are refractory to treatment [ 9 ]. Stadler et al reported a case of recurrent neck infections with long-term misdiagnosis for 24 years before the correct diagnosis of fourth branchial cleft anomaly was made [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Acute suppurative thyroiditis (AST), an inflammatory disease of the thyroid gland, is extremely rare in adults, since they typically exhibit a strong resistance to local infection ( 1 ). Thyroid abscesses are more likely to occur in children in instances of congenital anomaly ( 2 ). The majority of AST cases are caused by Gram-positive Streptococcus species ( 3 ).…”
Section: Introductionmentioning
confidence: 99%